AKURASI HASIL TERJEMAHAN KLAUSA PASIF DALAM TEKS MAULIDULBARZANJIY KARYA A’S-SAYYID JA‘FAR AL-BARZANJ - Titik Yulianti (CMES (Center of Middle Eastern Studies), 2014)
This research is trying to analyze the translation of passive clause arrangement patterns and its results accuracy in Maulidul-Barzanjiy text. The objectives of this research are: (1) to describe translation product of passive clauses in Maulidul-Barzanjiy text, (2) to measure translation product accuracy inMaulidul-Barzanjiy text based on meaning equivalence. The method used in this research is descriptive qualitative one. The data sources are Maulidul-Barzanjiy text by Sidqi and Anwar (2013) and five respondents. In the first problem, the data were collected by non-interactive method: selecting passive clauses from target text which have translation equivalences with source text. Meanwhile, in the second problem, the data were collected by interactive method using questionare and interview to five respondents. There are five patterns of clauses arrangement patterns found, they are: fuʻila-yufʻalu mafʻūl al-fiʻlul-maʻlūm+dhamīr  ismul-mashdar+ dhamīr wal-makān wal-chāl+dhamīr shīghatul- and ismu‘z-zamān.Comparative descriptive analysis is used for analyzing the data analysis in the first problem, while the second one is analyzed by using interactive model, including data reduction, data display, and verification. The result of this study can be concluded as follows: first, passive clause in Maulidul-Barzanjiy text has five patterns of arrangement. The comparison of all patterns is 27% derived from fiʻl majhūl whereas 73% derived from fiʻl maʻlūm, shīghah mafʻūl, ism mashdar, ism zamān, ism makān, and chāl. Second, the translation of Maulidul-Barzanjiy text is accurate. Its accuracy score is 2,6 from decimal completing of 2,560256. The score appeared because of source text was translated to target text without meaning distortion, namely addition and deletion in translating text which can change meanings. Addition and deletion in translating text are merely aimed to help readers comprehend the translation product.